Intensification of management decision making in socially responsible systems using AI - N. P. Kharchenko (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Modern socially responsible systems (SRS) operate in conditions of low uncertainty and rapid changes in the external environment, which predetermines the need for prompt and high-quality management decision-making. These systems are focused on the opinions of a wide range of international parties, stakeholders – employees, consumers, partners and society. It seems appropriate to conduct a multi-criteria and comprehensive study of the application of artificial intelligence (AI) technologies with the projection of accelerating management processes, increasing their validity and efficiency.Goal. Algorithmization of approaches to managing socially responsible systems and installation of methods for their interpretation using AI technologies.Materials and methods. The work used materials from periodicals, analyzed scientific publications on the problems of managing socially responsible systems using artificial intelligence, Internet resources, analytical reviews. During the study, methods of graphical and tabular presentation of results, the method of comparative analysis, collection and systematization of data on the topic of the study were used.Results and discussions. During the study, the author analyzed the role of artificial intelligence in overcoming the challenges of socially responsible management systems. The analysis showed the obstacles in the transparency of reporting of modern companies. Quantitative analysis made it possible to accumulate the best global practices of integrating artificial intelligence in the direction of intensifying management decision-making and acquiring significant advantages in managing socially responsible systems.Conclusion. Conclusions are made based on the conducted research and measures are proposed to reduce the level of risks and dangers from the use of AI in management decisions.